Modified quad helix appliance for thumb sucking and cross bite correction - C Vinay; V Sandeep; C H Hanumanth Rao; K S Uloopi; A Siva Kumar (Wolters Kluwer Medknow Publications, 2013)
Digit sucking habit is a learned pattern of behavior commonly seen in children of preschool age. Prolonged digit sucking beyond the preschool age, lead to the development of malocclusion such as anterior open bite, maxillary constriction and posterior crossbite. Treatment strategies include interception of habit and correction of the malocclusion. The present case report describes a modified quad helix appliance used successfully in a 9-year-old child to intercept thumb sucking habit and simultaneous correction of posterior crossbite. The appliance has the advantage of easy fabrication, being versatile and more patients compliant.